2017
DOI: 10.1016/j.bpj.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effect of Profilin Impacts the Formin mDia1 Force-Sensing Mechanism in Actin Polymerization

Abstract: Formins are force-sensing proteins that regulate actin polymerization dynamics. Here, we applied stretching tension to individual actin filaments under the regulation of formin mDia1 to investigate the mechanical responses in actin polymerization dynamics. We found that the elongation of an actin filament was accelerated to a greater degree by stretching tension for ADP-G-actin than that for ATP-G-actin. An apparent decrease in the critical concentration of G-actin was observed, especially in ADP-G-actin. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 30 publications
11
58
0
Order By: Relevance
“…In all these configurations, individual formins behaved similarly in terms of elongation rate (figure 1B) and processivity ( figure 1C). These results are in agreement with previous reports for glass-anchored formins (Cao et al, 2018;Jégou et al, 2013;Kubota et al, 2017) . In the lipid-anchored formin configuration, the microfluidics flow dragged the filament-elongating formins to the edge of the lipid pattern, where their activity was unaffected.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…In all these configurations, individual formins behaved similarly in terms of elongation rate (figure 1B) and processivity ( figure 1C). These results are in agreement with previous reports for glass-anchored formins (Cao et al, 2018;Jégou et al, 2013;Kubota et al, 2017) . In the lipid-anchored formin configuration, the microfluidics flow dragged the filament-elongating formins to the edge of the lipid pattern, where their activity was unaffected.…”
Section: Resultssupporting
confidence: 94%
“…In cases where the leading filament buckled between the leading and trailing formin attachment points, the buckling force was estimated to be lower than 0.15 pN (see Methods). For trailing formins, this force adds up to the minimal viscous pulling force applied to the trailing filament, and is expected to accelerate elongation, not slow it down (Jégou et al, 2013;Kubota et al, 2017;Yu et al, 2017) . We therefore concluded that the applied forces are negligible and likely play no role in the slowing down of formin elongation rates.…”
Section: Anchoring Formins To a Solid Surface Further Hinders Their Amentioning
confidence: 99%
See 1 more Smart Citation
“…is, most likely, the configuration after addition of a new profilin‐actin subunit and prior to the stepping forward of the lagging FH2 domain of the dimer, in preparation to accept the next subunit . Specifically, this corresponds to the addition of a new subunit in the ‘stair‐stepping model’ .…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of Cdc12-mediated actin polymerization by myosin pulling was an important assumption to prevent node clump formation in the first formulation of the SCPR model [5] (later models incorporating additional mechanisms, such as actin filament cross-linking, reproduced ring assembly without relying on such mechanosensing [13]). However, recent experimental studies testing formin mechanosensitivity [1416] showed extensional forces on the FH1 domains promote, rather than inhibit, profilin-regulated actin polymerization by mouse formin mDia1 [15,16] and budding yeast formin Bni1 [14]. …”
mentioning
confidence: 99%